2021
DOI: 10.1371/journal.pntd.0009551
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neutralising antibodies against SARS-CoV-2 in acute infection and convalescence: A systematic review and meta-analysis

Abstract: Background Individuals infected with SARS-CoV-2 develop neutralising antibodies. We investigated the proportion of individuals with SARS-CoV-2 neutralising antibodies after infection and how this proportion varies with selected covariates. Methodology/Principal findings This systematic review and meta-analysis examined the proportion of individuals with SARS-CoV-2 neutralising antibodies after infection and how these proportions vary with selected covariates. Three models using the maximum likelihood method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Immunogenicity of vaccines can be evaluated through different serum and cellular markers that exhibit a range of kinetics and evolutions over time. It became evident early on through the pandemic that neutralizing activity is highly correlated with anti-RBD IgG values [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] but an absolute conversion factor could not be established. That may in part be due to major inter-studies heterogeneity as to the kind of patients (COVID-19 experienced vs. COVID-19 naive), immune binding assays and neutralization assays that were implemented, making comparisons unreliable, in part to apparent divergent kinetics of neutralizing and anti-RBD Abs that some studies highlighted [16] , [22] , [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunogenicity of vaccines can be evaluated through different serum and cellular markers that exhibit a range of kinetics and evolutions over time. It became evident early on through the pandemic that neutralizing activity is highly correlated with anti-RBD IgG values [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] but an absolute conversion factor could not be established. That may in part be due to major inter-studies heterogeneity as to the kind of patients (COVID-19 experienced vs. COVID-19 naive), immune binding assays and neutralization assays that were implemented, making comparisons unreliable, in part to apparent divergent kinetics of neutralizing and anti-RBD Abs that some studies highlighted [16] , [22] , [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%
“…While quantitative binding assays only identify physical interactions and are mainly used for diagnostic purposes, functional neutralizing activity can only be directly investigated by means of VNTs platforms, that are grossly divided into direct VNTs, which require viable virions of SARS-CoV-2 and are considered the gold standard, and surrogate (s)VNTs, based on binding competition assays between antibodies and target receptors that mediate viral attachment and entry. Studies available so far have shown a significant degree of correlation between anti-S-RBD Abs levels and serum neutralizing bioactivity as assessed by VNTs [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , nonetheless some other studies have remarked that this correlation might change over time due to affinity maturation of humoral response, thus limiting the absolute quantitative value of anti-S-RBD Abs as a reliable COP [15] , [16] , [22] , [23] , [24] , [25] , [26] . In fact, waning of binding Abs either after natural infection or vaccination might be countered by the maintenance of neutralizing capacity by ongoing affinity maturation of Spike-specific B lymphocytes [27] .…”
Section: Introductionmentioning
confidence: 99%
“…The S protein of SARS-CoV-2 interacts with hACE2 with a dissociation constant (K d ) of several tens of nano-molars, based on surface plasmon resonance (SPR) analysis; this is ~10-to 20-fold higher than that of SARS-CoV [5,10,11]. Neutralizing antibodies, which bind to the S protein and prevent its interaction with ACE2, are useful for preventing viral infection [12][13][14]. Vaccines, which ideally produce neutralizing antibodies against the S protein, are an extremely useful way to produce immunity for the prevention of SARS-CoV-2 [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…NAbs are detectable in 85% of patients after recovery from SARS-CoV-2 infection (79,80). This proportion was higher among patients with severe SARS-CoV-2 infection and lower in asymptomatic infections (80).…”
Section: Antibody Responses During Acute Sars-cov-2 Infectionmentioning
confidence: 97%
“…NAbs are directed against either the RBD or the NTD, both being located on the S1 subunit of the S protein (77,78). NAbs are detectable in 85% of patients after recovery from SARS-CoV-2 infection (79,80). This proportion was higher among patients with severe SARS-CoV-2 infection and lower in asymptomatic infections (80).…”
Section: Antibody Responses During Acute Sars-cov-2 Infectionmentioning
confidence: 99%